Muscle Dysmorphia and the Perception of Men’s Peer Muscularity Preferences - Linda Lin PhD; Frank DeCusati BA (American Journal of Men's Health, 2016)
Research suggests that peer muscularity norms preferences are related to men’s body image, but little information is known about how perceptions of specific peer group norms preferences are related to men’s body image disturbances and specific health behaviors. This study investigated how men perceived the muscularity preferences of male, female, close, and distant peers and whether the perceptions of specific peer preferences were related to muscle dysmorphia and steroid use. Data on muscle dysmorphia and the perceptions of peer muscularity norms were collected from 117 male college students. Results indicated that men perceived distant and male peers as having the most exaggerated preferences for muscularity and that those perceptions were not an accurate reflection of their distant male peers’ reported preferences. Results also indicated that perceptions of close female peer muscularity preferences were predictive of symptoms of muscle dysmorphia, but this relationship did not exist for other peer groups, suggesting that the perceptions of close female peer preferences may play a role in the development of muscle dysmorphia. No relationship was found between perceptions of peer muscularity preferences and steroid use.